Whole genome analysis of a schistosomiasis-transmitting freshwater snail - Coen M. Adema (Nature Portfolio, 2017)
Biomphalaria glabrata is a fresh water snail that acts as a host for trematode Schistosoma mansoni that causes intestinal infection in human. This work describes the genome and transcriptome analyses from 12 different tissues of B glabrata, and identify genes for snail behavior and evolution.